Traditional Medicine and Magic According to Some Ethiopian Manuscripts from European Collections - Burtea, Bogdan (Aethiopica, 2015)
The present paper is dealing exclusively with medico-magical texts and traditions from a Christian Ethiopian environment. The handbooks and collections of various traditional healers in Ethiopia have played a significant role in the chain of transmission of medical and magical knowledge. This paper will focus on the structure and composition strategy exemplified by four Ethiopian manuscripts (MS Or. 11390 from the British Library, MS Éthiopien 402, 402 and 648 from the Bibliothèque nationale Paris). The analysis shows how the specialist knowledge was transmitted, preserved and reused. Moreover, it sheds some light on the protagonists of this transfer.